(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Present concerning facts of Dengue virus has proved this as a worldwide emerging threat, which causes Dengue fever.This is an illness not sufficiently covered in medical curriculum and there is no universally acceptable significant diagnostics, vaccines or treatments of Dengue fever. It has become crucial to develop a novel, affordable diagnostic tools, therapeutics and vaccines based on the available clinical experience Dengue complete genome. The promoter is one of the regions of DNA sequence where RNA polymerase first attaches during the initiation of transcription. For gene expression, the promoter acts as an important site. There are severe outbreaks of Dengue in Bangladesh and clearly there is a lack of sufficient anti-viral drug and vaccine against this virus. In this research,we have analyzed of all verified Dengue genome sequences of Bangladesh, available in National Center of Biotechnology Information (NCBI), USA and other authenticdatabases, to look for potential promoters for vaccine and therapeutic applications.